EVALUATION OF THE ROUGHER FEED AND CONCENTRATE SIZE DISTRIBUTIONS FROM THE SALOBO SULPHIDE COPPER ORE PROCESSING PLANT - Fonseca, Ronaldo Almeida; Olegario Júnior, Francisco das Chagas; Bergerman, Mauricio Guimarães (HOLOS, 2017)
Salobo plant processes a gold and copper sulfide ore. The flotation process comprises the rougher, cleaner, and scavenger stages. Concentrate from the rougher and scavenger stages goes through a regrinding process before being fed into the cleaner stage. During the first years of operation, it was noticed that the regrinding feed size was consistently finer than expected, even though the flotation feed size (rougher stage) was within the planned parameters and significantly coarser than the concentrate from the rougher stage. This paper describes the results of field samplings and laboratory tests carried out to identify the factors behind such difference and to quantify it. Moreover, it shows the impacts of such size difference on the concentrate regrinding stage.